Emerging in‐plane anisotropic two‐dimensional materials. Issue 1 (24th April 2019) - Li, Liang; Han, Wei; Pi, Lejing; Niu, Ping; Han, Junbo; Wang, Chengliang; Su, Bin; Li, Huiqiao; Xiong, Jie; Bando, Yoshio; Zhai, Tianyou
Abstract: Black phosphorus (BP) is a rapidly up and coming star in two‐dimensional (2D) materials. The unique characteristic of BP is its in‐plane anisotropy. This characteristic of BP ignites a new type of 2D materials that have low‐symmetry structures and in‐plane anisotropic properties. On this basis, they offer richer and more unique low‐dimensional physics compared to isotropic 2D materials, thus providing a fertile ground for novel applications including electronics, optoelectronics, molecular detection, thermoelectric, piezoelectric, and ferroelectric with respect to in‐plane anisotropy. This article reviews the recent advance in characterization and applications of in‐plane anisotropic 2D materials. Abstract : In‐plane anisotropic 2D materials, which possess low‐symmetric structures and anisotropic properties, are emerging as a new family of 2D materials. The recent progress in characterizations and applications of in‐plane anisotropic 2D materials are reviewed. Viewpoints on the current challenges and future research directions on this rapidly emerging research field are discussed.